The influence of three-year symmetrical training on the precision and frequency of the fencers` movement - Johne, M. (Central European Journal of Sport Sciences and Medicine, 2023)
The assessment and comparison of the precision and frequency of movement in épée fencers representing various sport classes, and the determination of the influence of three-year symmetrical and unilateral training on dynamic asymmetry. Material and Methods: The research was conducted in 60 female épée fencers, who were divided into four groups according to the sport class they represent (n= 15). In group I there were medalists of the World and European Championships, in group II - medalist of the Polish Championships. Group III and IV consisted of players who achieved successes at the Warsaw Championships. After three years of symmetrical training, the tests were repeated in groups III and IV. The tests were carried out using the Vienna Test System with the aid of the Motor Performance Series device (S2 test), which allows the assessment of coordination skills in terms of fine motor skills. Results: In the conducted research, significant differences in the asymmetry of the upper limbs in the aiming and tapping tests were found in all data groups. The differences in the tests obtained with the dominant and non-dominant upper limb confirm the greatest dynamic asymmetry in the female fencers from the Masters Class. After three years of symmetrical training in the experimental group and unilateral training in the control group, statistically significant differences were observed in all the trials performed with the dominant and non-dominant upper limb. However, in the experimental group of épée fencers, the dynamic asymmetry in the aiming indicators was lower than in the control group. Conclusions: Dynamic asymmetry in terms of the precision and frequency of movement was recorded in all studied groups. High-class épée fencers were characterized by the most significant difference between the results obtained with the dominant and non-dominant upper limbs, which is the result of long-term unilateral training. The three-year symmetrical training conducted in the experimental group had a positive effect on the precision and frequency of movement, however, it did not prevent the occurrence of dynamic asymmetry in the participants. The unilateral training used in the control group further increased the asymmetry of movement in the sportswomen.